Bouwvakkers protesteren op de dam tegen de inhouding van 2% op de uitbetaling van de vakantiebonnen - Bennekom, Kors van,
Bouwvakkers protesteren op de dam tegen de inhouding van 2% op de uitbetaling van de vakantiebonnen.